2015
DOI: 10.1007/s12262-015-1409-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Rib Fracture Fixation in Patients with Flail Chest and Multiple Non-flail Rib Fractures

Abstract: The purpose of this study is to evaluate the potential benefits of rib fracture fixation in patients with flail chest and multiple non-flail rib fractures versus conventional treatment modalities. A retrospective reviewed study compared 86 cases which received surgical treatment between June 2009 and May 2013 to 76 cases which received conservative treatment between January 2006 and May 2009. The patients were divided into the flail chest (n=38) and multiple non-flail rib fracture groups (n=124). In the flail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 28 publications
0
32
0
2
Order By: Relevance
“…Surgery is the predominant method of treatment for severe thoracic trauma (22). For patients with associated multiple fractures of multiple ribs, the fractured ribs should be fixed to improve the respiratory and circulatory function of the patients (23,24). Several implants have been particularly designed for the fixation of fractured ribs.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is the predominant method of treatment for severe thoracic trauma (22). For patients with associated multiple fractures of multiple ribs, the fractured ribs should be fixed to improve the respiratory and circulatory function of the patients (23,24). Several implants have been particularly designed for the fixation of fractured ribs.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis demonstrated that patients with painful, multiple rib fractures, that were not flail, benefit from surgical stabilisation with regards to pain, respiratory function and socio-professional disability (17). A more recent study corroborated these findings and further demonstrated shorter hospital stay (11.1% vs. 15.9%, P=0.013), fewer respiratory infections (4.6% vs. 17.0%, P=0.025), and an earlier return to work (28 vs. 42 days, P=0.028) (18). A further multicentre, randomised control trial of surgical stabilisation of rib fractures in patients with non-flail fracture patterns is ongoing (19).…”
Section: The Role Of Surgical Fixation In Multiple Simple Rib Fracturesmentioning
confidence: 84%
“…According to Yang et al (15), mortality rate of the flail chest is approximately 16% which is increased if the flail chest is combined with a sternal fracture (16). Industry stepping into the advanced stage, multiple rib fractures combined with sternal fractures, with a rocketing growth of incidence rate and severe damage to human health, have become the focus of modern medicine (9,17). The advancement of the new internal fixation equipment makes the operation of patients with fractures easier and safer, for example, the nickel-titanium memory alloy, with its good histocompatibility to be deformed and deployed at low temperature and to automatically restore the original shape at body temperature, is of great help for the convenience of the fixation, the shortening of the operation time, the decrease of injuries around the fracture, and the maintenance of effective blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, after the above conservative treatments, patients often suffer from accumulated secretions in the respiratory tract, chest pain, tachypnea, and even dyspnea aroused from too long bed rest that will increase the risk of parenchymatous pneumonia such as acute pneumonia and persistent pneumonia, and also suffer from muscular atrophy due to easily occurring incomplete transposition or complete fractures, vulnerable to complications or recurrence of disease after treatment (7,8). With the innovation of medical technology and the advanced internal fixer with better performance, the nickel-titanium memory alloy internal fixer, has high safety, stability, maneuverability and convenience, which is able to narrow the wound, is a new type of treatment device for the flail chest (9,10). So far few studies on the efficacy of the method of internal fixation by the nickel-titanium memory alloy and the method of internal fixation by the partial pressure bandage in treating the flail chest caused by multiple rib fractures combined with sternal fractures have been reported, which inspired this study to investigate the efficacy of these two methods in the treatment of patients with multiple rib fractures combined with sternal fractures and make comparison of the postoperative adverse reactions and complications between the two methods.…”
Section: Introductionmentioning
confidence: 99%